دور الحزب الحاكم في ترسيخ الديمقراطية - دراسة حزب العدالة والتنمية التركي- - سواسي, ياسمين (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة موضوع دور الحزب الحاكم في ترسيخ الديمقراطية وتم اختيار حزب العدالة والتنمية التركي نموذجا لهذه الدراسة نظرا لما حققه هذا الحزب من انجازات على مختلف المستويات مجسدا بذلك عملية الترسيخ الديمقراطي. تم في هذه الدراسة التعرف على حزب العدالة والتنمية ومشروعه السياسي بالتطرق الى مجموعة الاصلاحات التي عرفتها تركيا خلال مدة حكمه, والتي أحدثت تغيرا على الصعيد السياسي والاجتماعي فأصبحت تركيا تمثل أقوى الاقتصاديات, وحققت نجاحا في مجال حقوق الانسان بمعالجتها للقضايا الداخلية وقلصت من دور المؤسسة العسكرية التي كانت تطغى على الحياة السياسية في تركيا هذا وقد خلصت الدراسة الى مجموعة من النتائج منها: - أن تركيا استطاعت ترسيخ الديمقراطية من خلال التطبيق الفعلي لبرامجها والقيام بإصلاحات حقيقية على مختلف المستويات. - شكّل سعي تركيا للدخول إلى الاتحاد الأوروبي نقطة إيجابية في عملية الإصلاح الداخلي. والانتقال نحو المسعى الديمقراطيAbstract: The study concentrated on the issue of the role of the ruling party in the consolidation of democracy , the study was chosen The Turkish Party of Justice and Development as a model , due to the achievements of this party at various levels to embodied the democratic consolidation process. The study identified the Turkish party of Justice and development and it's political project as the known reforms in Turkey during they stay in power , it makes a change in the political and social level so Turkey becomes one of the strongest economies, and it's success achieved in the field of human rights by solved their internal issues and reduced the military role which was overwhelm the political life in Turkey. the study concluded some of results which as : -Turkey has been able to consolidate democracy through the effective implementation of programs and carry out real reforms at various levels. - Turkey's effort to enter into the European Union was a positive point in the process of internal reform. And to move toward democratic endeavor. .
مدكرة ماستر